A comprehensive review of Interferometric Reflectance Imaging Sensor as a sensitive detection platform and its application areas - Bakhshpour-Yucel, Monireh; Unlu, Nese Lortlar; Seymour, Elif; Denizli, Adil (Biosensors and bioelectronics. X, 2025)
The Interferometric Reflectance Imaging Sensor (IRIS) technology represents a significant advancement in biosensing, providing a label-free, selective, sensitive, and high-throughput platform for detecting molecular interactions. This review explores the underlying principles, instrumentation, and diverse applications of IRIS, with a focus on its efficacy for real-time monitoring of DNA-protein and protein-protein interactions, as well as virus detection. IRIS can measure DNA hybridization kinetics and identify pathogens without labeling, highlighting its versatility and reliability in biomedical research and diagnostics. IRIS achieves enhanced sensitivity and specificity by leveraging spectral reflectivity as a transduction mechanism and employing a 3D polymeric surface chemistry for bioreceptor immobilization. The review underscores IRIS's potential to revolutionize clinical diagnostics, biomolecular screening, and the study of biomolecular binding affinities, establishing it as a powerful tool for future research and medical applications. •IRIS technology displays a label-free, selective, sensitive and high-throughput platform.•IRIS measures DNA hybridization kinetics and identify pathogens.•IRIS uses in diagnostics, biomolecular screening, and biomedical research.•IRIS can easily be used to identify bacterial and viral pathogens in complex samples with high precision.